To solve the system of equations using the elimination technique, we need to eliminate one of the variables. We can achieve this by multiplying the second equation by 2:
2(2x - y) = 2(3)
4x - 2y = 6
Now we have the two equations:
3x + 2y = 1
4x - 2y = 6
Adding these equations together, we eliminate the y variable:
(3x + 2y) + (4x - 2y) = 1 + 6
7x = 7
x = 7/7
x = 1
Now that we have found the value of x, we can substitute it back into one of the original equations to solve for y. Let's use the first equation:
3(1) + 2y = 1
3 + 2y = 1
2y = 1 - 3
2y = -2
y = -2/2
y = -1
So the solution to the system of equations is x = 1 and y = -1.
Solve the system of equations with the elimination technique. Please show your work.
3x + 2y = 1
2x - y = 3
2 answers
Use the elimination method to solve the follow system of equations.
9x−7y=22
x+3y=−24
This question requires you to show your work.
(1 point)
Responses
(0,−8)
open paren 0 comma negative 8 close paren
(4, 2)
(4, 2)
(−3,−7)
9x−7y=22
x+3y=−24
This question requires you to show your work.
(1 point)
Responses
(0,−8)
open paren 0 comma negative 8 close paren
(4, 2)
(4, 2)
(−3,−7)